A study of interlayer gallery of modified sodium montmorillonite (MMT) nanofiller using ion exchange and surfactant method - Mohamad Faiz, Mohamed Yatim (2012)
Polymer/layered-silicate hybrid nanocomposites have attracted strong interest in today’s materials research, as it is possible to achieve impressive enhancements of material properties compared to the pure polymers.This study aim is to modify the clay surface using ion exchange and surfactant methods before proceeding with fabrication of polymer nanocomposites.The polymer that used is Polylactic acid(PLA)because of its biodegradability characteristic. Organoclay will characterize by using Atomic Adsorption Spectrometry(AAS)and Fourier Transform Infrared Spectroscopy (FTIR).PLA-Nanocomposites were prepared by using solution casting and characterized by X-Ray Diffraction Analysis (XRD),Scanning Electron Microscopy(SEM).AAS analysis showed there is a transition metal ion in the interlayer of sodium montmorillonite(MMT)and it is confirmed with SEM analysis. The FTIR analysis for surfactant organoclay shows the presence of TEOS surfactant in the organoclay properties. The XRD analysis proved that the modification happens by the increasing of clay interlayer basal spacing.The XRD analysis for PLA-Nanocomposites showed that PLA is intercalated the interlayer gallery of organoclay to similar extents and also increased the d-spacing.The structure of polymer nanocomposites that came out of this research is intercalated and exfoliated nanocomposites.